Roman amphorae in Neuss : Augustan to Julio-Claudian contexts - Cesteros, Horacio González, (Roman and late antique Mediterranean pottery ;, 2018)
The occupation of the territories on both sides of the Rhine was an enormous logistical challenge for the Roman military administration. This text provides an in-depth study of the amphorae from Neuss, providing further understanding of the local area and the logistics of the Roman army and its supply from very distant areas.